The Influence of Mother's Education on Early Detection Knowledge of Toddler Development Aged 36-47 Months - Lumastari Ajeng Wijayanti; Warda M; Cakrawati R; Rezqiqah Aulia Rahmat; Sardi Anto (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Early detection of toddler development is a crucial step in identifying developmental delays early so that appropriate intervention can be implemented. Mothers play a key role in monitoring their children's development, which is influenced by their education level. Higher education is expected to improve mothers' ability to understand and perform early detection of toddler development. This study aims to determine the effect of maternal education on knowledge of early detection of toddler development in children aged 36–47 months. This study used quantitative methods with an analytical design and a cross-sectional approach. Sectional. The research sample was mothers who have toddlers aged 36–47 months in health service area X. Data were collected using a questionnaire and analyzed using the Chi- Square test. The results showed a significant influence between maternal education and knowledge of early detection of toddler development (p < 0.05). The conclusion of this study is that maternal education influences the level of knowledge of early detection of toddler development.